MODERNIZATION OF BUSINESS PROCESSES - E. A. Khlevnaya; A. P. Garnov (Модернизация, инновация, развитие, 2016)
Trends in modernization of business processes of the organization are discussed. Modernization is imperative in today’s innovation society because evolution of management systems has come to a period of flexible emergency decisions. The process management approach has already been adopted by a majority of companies. However, the choice of business process elements and their automation will not bring expected benefits till mechanisms of effective control over these elements are identified. The purpose of business process modernization is to transform the enterprise in such a way that information age and ideology control requirements realized through the process approach are met.